TENDENCIES OF MORTALITY AND LIFE EXPECTANCY IN UKRAINE BEFORE THE RUSSIAN FULL SCALE MILITARY INVASION - Kurylo, Iryna (Economy and Sociology, 2022)
The ambivalence of mortality and life expectancy dynamics in Ukraine is a significant and complex demographic problem. Our aim is to examine the last tendencies of mortality and life expectancy, analyse the level and dynamics of mortality by major causes of death before the Russian military invasion of Ukraine. This analysis constitutes a base for the further comparative estimation of demographic losses due to the war. Trends of sex- and age-specific mortality are considered. Specific characteristics of mortality in urban and rural settlements are analysed. We use the following methods: demographic rates, standardized death rates (European standard population), life tables, decomposition method, descriptive statistics, graphic method. Our findings suggest that following a period of growth in life expectancy (2009-2013) a period of fluctuation and stagnation (2014-2019) has started in Ukraine under the influence of political-military and economic factors. Beginning with 2020, life expectancy was additionally influenced by COVID-19. Noncommunicable diseases are among significant contributors to premature adult mortality in Ukraine. However, the excessive share of deaths (especially among men) is also related to external causes. The dynamics of mortality from cardiovascular diseases show a general trend of decline over the past fifteen years, however with fluctuations in the latest years. A deterioration has already taken place in 2020. There is a slight decrease in cancer mortality over the past fifteen years. The reduction in death rate from external causes in Ukraine over this period was significant. The standardized death rate from digestive diseases has increased with COVID-19 having played a leading role in the unfavorable changes of life expectancy over the past two years.